2011
DOI: 10.1002/ana.22473
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effect of inflammation on subventricular zone versus hippocampal precursors in brain injury

Abstract: Objective Inflammation promotes epidermal wound healing but is considered detrimental to recovery from CNS injury. Sick infants have increased levels of cytokines in their CSF that correlate with poor neurological outcome. In this study we investigated the role of neuroinflammation and more specifically, IL-6, in the amplification of subventricular zone (SVZ) and subgranular zone (SGZ) neural precursors after neonatal brain injury. Methods Neonatal hypoxia/ischemia (H/I) was induced in P6 rat pups and IL-6 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 78 publications
2
38
2
Order By: Relevance
“…Our results demonstrated a specific role of IL-1 in inflammatory-driven decreased neurogenesis in the hippocampus. This phenomenon was previously shown in other neurological conditions, including depression and stress (Covey et al, 2011;Crampton et al, 2011;Green et al, 2012;Yang and Levison, 2007;Zunszain et al, 2012). The fact that in our model, there was no additive effect when LPS and HI were combined suggest that they act through the same pathway or have redundant function, both through IL-1, with effects already maximal on their own.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results demonstrated a specific role of IL-1 in inflammatory-driven decreased neurogenesis in the hippocampus. This phenomenon was previously shown in other neurological conditions, including depression and stress (Covey et al, 2011;Crampton et al, 2011;Green et al, 2012;Yang and Levison, 2007;Zunszain et al, 2012). The fact that in our model, there was no additive effect when LPS and HI were combined suggest that they act through the same pathway or have redundant function, both through IL-1, with effects already maximal on their own.…”
Section: Discussionsupporting
confidence: 82%
“…However, the role of inflammation in neural stem cell proliferation is still controversial and might be age-dependent. Recent work by Covey et al revealed that neurogenesis seen in an animal model of HI at P6 was mediated by IL-6 expression and was decreased by broad anti-inflammatory administration (Covey et al, 2011). On the other hand, studies in adult animals showed deleterious effects of inflammatory mediators on neural progenitor proliferation (Monje et al, 2003;Vallières et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…First, many experiments investigating proliferation after injury have focused on the hippocampal subgranular zone [33,34] . However, hippocampal neural precursors are quite different from SVZ neural precursors [32] Thus, it is not surprising that subgranular zone cells respond differently after similar insults compared to SVZ neural precursors. Second, adult mouse SVZ cells proliferate significantly after injury [35] and in our studies the P14-injured mice exhibited higher proliferative rates in both the ipsilateral and contralateral hemispheres compared to P11 rats.…”
Section: Color Illustration Online Only!mentioning
confidence: 93%
“…This suggests that injury signals are produced in the damaged hemisphere and that the larger the injury the greater the stimulus. Another consideration is that injury signals are not only produced by cells residing in the injured tissue, but immune cells attracted to the wound will produce and release cytokines and growth factors that are known to affect SVZ cells [27][28][29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…Brain injury and neurodegeneration are characterized by the increase in amount of proinflammatory cytokines and numbers of activated microglia [57]. Since inflammation is a key pathological change observed in these conditions [58], it is a valuable therapeutic target in the treatment of brain injuries and neurodegeneration.…”
Section: Components Of Neuroinflammationmentioning
confidence: 99%